Induction chemotherapy using intra-arterial cisplatin plus systemic TS-1 for locally advanced resectable oral cancer: Preliminary experience in a single institute. Issue 1 (January 2015) - Imaue, Shuichi; Tomihara, Kei; Takei, Rie; Inoue, Sayaka; Tsuno, Hiroaki; Oura, Takehiro; Tomizawa, Gakuto; Nomura, Kuninori; Arai, Naoya; Noguchi, Makoto
Abstract This study aimed to assess the effects of induction chemotherapy (ICT) using intra-arterial high-dose cisplatin (CDDP) infusion and concurrent peroral tegafur (TS-1) for the management of locally advanced oral cancer. We analyzed 30 patients diagnosed with locally advanced oral squamous cell carcinoma who were treated at our university hospital from April 2007 to March 2011. Eleven patients were diagnosed with stage II tumors, 10 with stage III, and 9 with stage IVA. Six patients demonstrated complete response to ICT, and the overall response rate, including the partial response rate, was 77%. Definitive therapies comprised "wait and see" for 3 patients, chemoradiotherapy for 3, brachytherapy for 1, and ablation surgery for 23 (limited, standard, and extended surgeries in 9, 13, and 1 patients, respectively). Locoregional recurrence was observed in 7 patients, 4 of whom died. ICT can potentially predict good outcome in the management of locally advanced oral cancer. Definitive therapy should be determined on the basis of patients' response to ICT. Further investigations to determine the criteria indicating the appropriate therapy to be employed after ICT are required.